Analisis penjualan listrik prabayar dan pascabayar dalam meningkatkan laba pada PT PLN (Persero) Unit Pelayanan Pelanggan (UP3) Manado - Gosal, Sharon Gloria; Pontoh, Winston; Kalalo, Meily Y. B. (Riset Akuntansi dan Portofolio Investasi, 2025)
Sales are activities carried out by sellers in selling goods and services with the hope of making a profit from these transactions. This research aims to analyze the sale of prepaid and postpaid electrical energy in increasing profits at PT PLN (Persero) Customer Service Unit (UP3) Manado. The type of research used is descriptive qualitative with quantitative data types. The research results show that sales of prepaid and postpaid electrical energy have not been able to increase profits at PT PLN (Persero) Manado Customer Service Unit (UP3), where net profit experienced a decrease in certain periods of the year due to high operational expenses. As a solution from the sales side, PT PLN (Persero) Manado Customer Service Unit (UP3) should start increasing profits by improving customer service such as providing attractive promos and increasing sales of prepaid electricity. Meanwhile, in terms of operational expenses, PT PLN (Persero) Manado Customer Service Unit (UP3) should focus more on controlling costs and operational efficiency to ensure that profits can grow along with increasing sales.